2020
DOI: 10.1038/s41598-020-73965-6
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre, retrospective study of the efficacy and safety of nivolumab for recurrent and metastatic salivary gland carcinoma

Abstract: Although immune-checkpoint inhibitors (ICIs) are effective against various cancers, little is known regarding their role in salivary gland carcinoma (SGC) treatment. Therefore, we evaluated the efficacy and safety of nivolumab monotherapy in patients with recurrent and/or metastatic SGC. In this multicentre retrospective study, nivolumab (240 mg) was administered every 2 weeks. The overall response rate (ORR), progression-free survival (PFS), overall survival (OS), and safety were examined; the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 58 publications
8
28
0
Order By: Relevance
“…Regarding the primary tumor site, while we performed nivolumab therapy in patients not included in the CheckMate 141 trial, such as nasopharyngeal cancer, clinical outcomes were comparable to those included in the CheckMate 141 trial 1,7 . In patients excluded from the CheckMate 141 trial, the efficacy of nivolumab therapy has been reported with primary tumors at other sites, including the nasopharynx, while its efficacy is limited in the salivary gland cancer 5,[26][27][28] . However, there is insufficient evidence for the optimal systematic therapy for HNC other than squamous cell carcinoma (SCC).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the primary tumor site, while we performed nivolumab therapy in patients not included in the CheckMate 141 trial, such as nasopharyngeal cancer, clinical outcomes were comparable to those included in the CheckMate 141 trial 1,7 . In patients excluded from the CheckMate 141 trial, the efficacy of nivolumab therapy has been reported with primary tumors at other sites, including the nasopharynx, while its efficacy is limited in the salivary gland cancer 5,[26][27][28] . However, there is insufficient evidence for the optimal systematic therapy for HNC other than squamous cell carcinoma (SCC).…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab was approved for recurrent or metastatic head and neck cancer (R/M HNC) after platinum drug administration in Japan in March 2017. Further evidence of efficacy has since been obtained [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that pembrolizumab demonstrated promising antitumor activity and a manageable safety profile in patients with advanced, PD-L1positive SGC [ 50 , 51 ]. Other recent studies showed the effectiveness and safety of nivolumab for the treatment of SGC [ 26 , 52 ]. All of these findings suggest that immune checkpoint inhibitors have clinical efficacy in patients with SGC.…”
Section: Discussionmentioning
confidence: 99%